Formulation and Evaluation of Analaathi Thailam: A Polyherbal Formulation for Rheumatic Diseases (International Journal of Food and Nutritional Sciences, 2022)
Analaathi Thailam is one of the oldest and most successful formula in Siddha Medicine, to cure rheumatic diseases. The traditional formula for Analaathi Thailam consists of 13 ingredients, the main ingredientbeing the tuber of Plumbago indica and five leaf extract, six raw drugs and sesame oil. Rheumatism is one of the most common problem world-wide, having various causes and different pathogenesis. Analaathi Thailam is a Siddha polyherbal formula that alleviates rheumatic disease effectively. The main action of the ingredients encompasses but not limited to diuretic, laxative, carminative, blood purifying, febrifuge and demulcent